Profil Kemampuan Penalaran Kreatif Matematis Mahasiswa Calon Guru - Wahyu Hidayat; Ratna Sariningsih (Universitas Hamzanwadi, 2020)
This study aims to obtain an overview of the mathematical creative reasoning abilities of the prospective teacher. The ability of mathematical creative reasoning in this study is the ability of students to justify a statement on the grounds of the truth of a statement that is based on novelty, plausible, and mathematical foundation. This research approach is qualitative using Grounded Theory. The population in this study were all students participating in the Calculus class of the Study Program Mathematics Education at one of the universities in West Java. In a while, the sample of 55 students was selected by a cluster random sampling technique. The results showed that students' mathematical creative reasoning abilities were categorized into three levels of ability based on the quality of the four categories, namely the initial step, the flow of completion, the related concepts, and the mathematical term errors.